Amidinate based indium(iii) monohalides and β-diketiminate stabilized In(ii)–In(ii) bond: synthesis, crystal structure, and computational study. Issue 40 (7th October 2020) - Banerjee, Samya; Dutta, Sayan; Sarkar, Samir Kumar; Graw, Nico; Herbst-Irmer, Regine; Koley, Debasis; Stalke, Dietmar; Roesky, Herbert W.
Abstract : Synthesis, crystal structure and DFT study of β-diketiminate stabilized In(ii )–In(ii ) bond and bis(amidinato)indium(iii ) monohalides. Abstract : Synthesis and bonding aspects of mononuclear bis-amidinate indium(iii ) monohalides L2 InX (1–3 ), where L = PhC(N t Bu)2 ; X is F (1 ), Br (2 ) or I (3 ) and β-diketiminate (NacNac) stabilized In(ii ) dimer ( Mes NacNac)2 In2 Br2 (4 ) with In–In bond are reported along with the single-crystal X-ray structures of 2–4 .